APPLICATION OF GEOINFORMATION SYSTEMS FOR THE SOLVING TASKS OF NAVIGATION SUPPORT FOR THE ARMIES - Lukiyanchuk, A.; Miroshnichenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
Rapid implementation of computer and information technologies in the activities of the troops (forces) is currently taking place, namely, significant successes in the use of geographic information systems (GIS) are noted. Modern GIS in the armed forces of other countries has also found wide application in the operational training of military C2 bodies, information support of combat actions, updating topographic maps, determining the location of the position of troops and individual servicemen, as well as in other areas of military activity. Therefore, it is necessary to analyze the most successful technologies and move towards their implementation. Currently, a large part of geographic information changes rapidly with time, which makes the use of traditional maps irrelevant. GIS is a software and technical complex that allows you to combine a model image of the territory with tabular information. The software and technical complex provides automated collection, processing, analysis, storage, display and distribution of spatially coordinated information. A computer system that makes it possible to edit, use, store, analyze and display graphic data in a cartographic form. GIS provide the most complete creation and timely restoration of the cartographic base. First of all, it concerns different types of cards. In addition, it is now possible to receive aerial, photographic and space images of local objects with minimal time delay, with the possibility of obtaining their specific characteristics. The speed of receiving information can only be guaranteed by a modern automated system with the possibility of documenting the provided information. The system allows you to create vector, raster and matrix maps, as well as quickly update various information about the area.